Screening Fitokimia Awal (Analisis Qualitative) Pada Daun Gambir (Uncaria Gambir Roxb) Asal Siguntur Muda - Melati Melati; Hesty Parbuntari (Jurnal Periodic Jurusan Kimia UNP, 2022)
Gambir (Uncaria gambir Roxb) belongs to family Rubiaceae and genus Uncaria. The content of chemical compounds in plants is called phytochemicals. Plants can be a source of chemical compounds that can be used as medicine.More than 80% of gambier production in Indonesia comes from the province of West Sumatra ,one of them in Siguntur Muda.Therefore, secondary metabolites in Gambir Leaves  have the potential to be further investigated as a source of bioactive compounds. The phytochemical screening of Gambir leaves is a preminilary qualitative test that needs to be done to maximise its function as a medicinal plant. Based on the result data of phytochemical screening show that Gambir contain secondary metabolite compounds of alkaloids, flavonoid, terpenoid and saponins, but do not contained steroid compound